(untitled) (SCIÉNDO INGENIUM, 2022)
It was determined how the Early Termination in environmental crimes is effective and compensatory to the environment. Frequency and procedural status of these crimes were recorded in the Specialized Prosecutor for Environmental Matters in Chachapoyas, during 2014-2020. In the FEMA information registry, 34 cases were verified in which early termination was applied, which represents a low number. Likewise, it is observed that early termination occurs in non-serious crimes, which do not require greater diligence, for which the custodial sentence is not applied, and with respect to civil compensation, the accused have complied with 100% of their cancellation. It is concluded that the most frequent criminal type is 310th of the Penal Code, crimes against forests and forest formations. On the other hand, there is no recidivism and there is speed in the processes. It is recommended that the substantiated report established in article 149 of Law 28611 be mandatory and that the compensation calculation for environmental damage be established as part of the content of the substantiated report in order to have an approximation to the valuation of the damage.